A lead-free resistance paste, a preparation method and application thereof

By combining ruthenium oxide and additives in lead-free resistor paste, the problems of poor TCR and ESD performance in resistor paste are solved, achieving environmental friendliness and excellent electrical performance, suitable for thick film resistors and hybrid circuits.

CN117766193BActive Publication Date: 2026-11-06CHAOZHOU THREE CIRCLE GRP CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311846317.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-29
Publication Date
2026-11-06
Estimated Expiration
2043-12-29

AI Technical Summary

Technical Problem

Existing resistive pastes contain lead components, which cause environmental pollution. At the same time, it is difficult to maintain the temperature coefficient of resistance (TCR) within ±100ppm/℃, resulting in poor antistatic performance (ESD) of electronic devices.

Method used

Lead-free resistive paste is used, containing ruthenium oxide as the conductive phase. By adjusting the mass ratio and particle size ratio of the first and second additives, the composition of the conductive and glass phases is optimized to ensure excellent ESD performance and TCR within the range of ±50ppm/℃.

Benefits of technology

It achieves the environmental friendliness and excellent ESD performance of lead-free resistor paste, while the TCR is within ±50ppm/℃, meeting the performance requirements of electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004639854070000051
    Figure BDA0004639854070000051
  • Figure BDA0004639854070000061
    Figure BDA0004639854070000061
  • Figure BDA0004639854070000071
    Figure BDA0004639854070000071
Patent Text Reader

Abstract

The application discloses a lead-free resistance paste and a preparation method and application thereof, and belongs to the technical field of electronic paste. The mass ratio of a first additive and a second additive, the mass ratio of ruthenium oxide, the first additive and the second additive, and the particle size ratio of the first additive and the second additive are regulated in the lead-free resistance paste, so that the ESD performance of a thick film resistor coated by the lead-free resistance paste is excellent, and the TCR width is relatively narrow and is within ±50ppm / ℃. Meanwhile, the lead-free resistance paste does not contain a lead-containing component, and can meet the environmental protection requirement of electronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of electronic pastes, specifically relating to a lead-free resistor paste, its preparation method, and its application. Background Technology

[0002] Resistive pastes are widely used in electronic components of thick-film resistors and thick-film hybrid circuits. Existing technologies typically prepare resistive pastes by dispersing inorganic powders such as conductive components, inorganic additives, and inorganic binders in an organic medium. The selection of inorganic additives and conductive components largely determines the electrical properties of thick-film resistors, and inorganic binders, such as glass, play an important role in maintaining the integrity of the thick film and its adhesion to the substrate.

[0003] Traditional resistive pastes used in thick-film resistors often employ lead-containing components, such as conductive oxides like lead ruthenate, to improve the resistor's electrical performance. However, the use of lead-containing materials in commercial products leads to environmental problems. If lead-free components are used to replace the original lead-containing components, it becomes difficult to maintain the temperature coefficient of resistance (TCR) within ±100ppm / ℃, and the electrostatic discharge (ESD) performance of electronic devices is also worse.

[0004] In response to the problems existing in the aforementioned resistive pastes, the current research focus in the field of electronic pastes is to find a resistive paste that does not contain lead components and can guarantee the TCR and ESD compliance of electronic devices such as resistors. Summary of the Invention

[0005] The purpose of this application is to overcome the shortcomings of the prior art and provide a lead-free resistor paste, its preparation method and application. The lead-free resistor paste can enable the resistors and other electronic devices to have excellent TCR range and ESD performance, while meeting the environmental protection requirements of electronic devices.

[0006] To achieve the above objectives, the technical solution adopted in this application is as follows:

[0007] A lead-free resistor paste, the lead-free resistor paste comprising inorganic components and organic components;

[0008] The inorganic components include a conductive phase, a glassy phase, and inorganic additives;

[0009] The organic components include resins, organic solvents, and organic additives;

[0010] The conductive phase includes ruthenium oxide;

[0011] The inorganic additive includes a first additive and a second additive; the first additive includes at least one of copper oxide and cuprous oxide, and the second additive includes at least one of niobium oxide, tantalum oxide, manganese oxide, titanium oxide, and iron oxide; the mass ratio of the first additive to the second additive is first additive: second additive = 1:(2~5).

[0012] This application adds ruthenium oxide as a conductive phase to the resistor paste, overcoming the problem that current resistors use conductive oxides such as lead ruthenate as conductive phases, resulting in lead content in the product and environmental pollution.

[0013] This application achieves superior ESD and TCR performance in the final product through the combined action of the first and second additives. In this application, the first additive can positively adjust the TCR, and the second additive can negatively adjust the TCR, while simultaneously improving ESD performance. Therefore, the combination of the two overcomes the problems of difficulty in maintaining TCR within ±100ppm / ℃ and poor ESD performance in lead-free resistor pastes.

[0014] The inventors discovered that only when the mass ratio of the first additive to the second additive is within the aforementioned range can the technical effect of both optimizing the ESD performance of the final product and maintaining the TCR within the range of ±50ppm / ℃ be achieved. If too much of the first additive is added, it will have a deteriorating effect on ESD, while if too much of the second additive is added, it will lead to problems such as a negative TCR and increased resistance. Therefore, by adjusting the mass ratio of the first additive to the second additive to 1:(2~5), the TCR width can be optimized within the range of ±50ppm / ℃ while ensuring a significant improvement in ESD performance.

[0015] In a preferred embodiment of the lead-free resistor paste of this application, the mass ratio of ruthenium oxide to the first additive and the second additive is ruthenium oxide: first additive: second additive = 1:(0.05~0.25):(0.2~0.6). Through extensive experiments, the inventors discovered that the first and second additives, as external oxides, affect the resistance, TCR, and other characteristics of the product by influencing the sintering behavior of the glass component in the resistor body. This application further improves these properties by controlling the mass ratio of ruthenium oxide in the conductive phase to the first and second additives in the inorganic additives. The ESD performance of the product is affected by the following: When the mass ratio of ruthenium oxide to the first and second additives is too small, that is, when the amount of the first and second additives added is too large, the conductive chains in the resistive element will be loosely distributed, and the conductor will be broken down, resulting in a deviation in ESD performance. When the mass ratio of ruthenium oxide to the first and second additives is too large, that is, when the amount of the first and second additives added is too small, the conductive particles in the resistive element will not be easily dispersed evenly, and there will be more soft agglomerated conductive particles. After high voltage discharge, the impedance of the soft agglomerated state will be conducted, which will also lead to the deterioration of ESD performance.

[0016] In a preferred embodiment of the lead-free resistor paste of this application, the particle size ratio of the first additive and the second additive is first additive: second additive = 1:(0.3~1). The inventors have found through numerous experiments that the physicochemical properties of the first additive and the second additive, as external oxides, also affect ESD performance. By controlling the particle size ratio of the first additive and the second additive, the ESD performance of the product can be further optimized, while satisfying the TCR within the range of ±50ppm / ℃. If the particle size ratio of the first additive and the second additive is too small, that is, the particle size of the first additive is too small relative to the second additive, the ESD effect will be significantly worsened. If the particle size ratio of the first additive and the second additive is too large, that is, the particle size of the first additive is too large relative to the second additive, it will lead to a larger sheet resistance of the resistor paste and a positive increase in the TCR of the product. Therefore, by limiting the particle size ratio of the first additive and the second additive to 1:(0.3~1), ESD can be further improved, while satisfying the TCR width within the range of ±50ppm / ℃.

[0017] In a preferred embodiment of the lead-free resistor paste of this application, the ruthenium oxide has a specific surface area of ​​10–70 m². 2 / g; The specific surface area of ​​the conductive phase ruthenium oxide described in this application is selected according to the resistance value requirement range of the resistor product. When the resistance of the resistor is 100Ω to 1KΩ, the specific surface area of ​​the ruthenium oxide is 40m² to 70m². 2 / g, when the resistance of the resistor is 1-10KΩ, the specific surface area of ​​the ruthenium oxide is 10-40m². 2 / g.

[0018] As a preferred embodiment of the lead-free resistor paste of this application, it includes at least one of the following (a) to (c):

[0019] (a) The resin includes at least one of methylcellulose, ethylcellulose, acrylic resin, epoxy resin and alkyd resin.

[0020] (b) The organic solvent includes at least one of terpineol, diethylene glycol monobutyl ether, tributyl citrate, diethylene glycol dibutyl ether, butyl carbitol and dibutyl phthalate.

[0021] (c) The organic additives include at least one of polyethylene wax, polypropylene wax, polyamide wax, hydrogenated castor oil, organobentonite, polyamide, polyacrylate, phosphate ester, organosiloxane, polyether, polyethylene glycol and polydimethylsiloxane.

[0022] As a preferred embodiment of the lead-free resistor paste of this application, based on the total mass percentage of the resistor paste being 100%, the mass percentage of the inorganic component is 50% to 70%, and the mass percentage of the organic component is 30% to 50%.

[0023] As a preferred embodiment of the lead-free resistive paste of this application, based on the total mass percentage of inorganic components being 100%, the mass percentage of the conductive phase is 5% to 40%, the mass percentage of the glass phase is 50% to 90%, and the mass percentage of the inorganic additives is 0.1% to 20%.

[0024] As a preferred embodiment of the lead-free resistor paste of this application, based on a total organic component mass percentage of 100%, the resin mass percentage is 1% to 20%, the organic solvent mass percentage is 60% to 90%, and the organic additive mass percentage is 0.5% to 20%.

[0025] As a preferred embodiment of the lead-free resistor paste of this application, the glass phase, with a total mass percentage of 100%, comprises the following components in the following mass percentages: SiO2 30%–56%, CaO 0–10%, Al2O3 1%–25%, ZnO 1%–20%, BaO 0–10%, SrO 0–10%, B2O3 5%–30%, and Na2O 9%–11%.

[0026] As a preferred embodiment of the lead-free resistor paste of this application, the inorganic additives further include at least one of silicon oxide, aluminum oxide and zirconium silicate.

[0027] In a preferred embodiment of the lead-free resistive paste of this application, the average particle size of the conductive phase is 0.1 to 10 μm; the average particle size of the glass phase is 0.5 to 2 μm; and the average particle size of the inorganic additives is 0.1 to 5 μm.

[0028] Secondly, this application also provides a method for preparing the lead-free resistor paste, comprising the following steps:

[0029] (1) The resin is heated and dissolved in an organic solvent, then an organic additive is added, and the organic carrier is obtained after filtration and cooling.

[0030] (2) Mix and disperse the components in the inorganic component to obtain an inorganic mixed powder;

[0031] (3) The inorganic mixed powder is added to the organic carrier and dispersed evenly to obtain the lead-free resistor paste.

[0032] Compared with the prior art, the beneficial effects of this application are as follows:

[0033] This application achieves superior ESD performance and a narrower TCR width (within ±50ppm / ℃) in thick-film resistors by adjusting parameters such as the mass ratio of the first and second additives, the mass ratio of ruthenium oxide to the first and second additives, and the particle size ratio of the first and second additives in the lead-free resistor paste. Furthermore, the lead-free resistor paste described in this application does not contain lead-containing components, thus meeting the environmental protection requirements for electronic devices. Detailed Implementation

[0034] To better illustrate the purpose, technical solution, and advantages of this application, the following will provide further explanation of this application in conjunction with specific embodiments.

[0035] Unless otherwise specified, the reagents, methods and equipment used in this application are all conventional reagents, methods and equipment in this technical field.

[0036] Examples 1-25

[0037] The formulations of inorganic additives in the lead-free resistor pastes described in Examples 1 to 25 of this application are shown in Table 1, the formulations without organic components are shown in Table 2, the formulations of the glass phase are shown in Table 3, the formulations of organic components are shown in Table 4, and the formulations of the lead-free resistor pastes are shown in Table 5. The preparation method of the lead-free resistor paste includes the following steps:

[0038] (1) At 80℃, the resin was uniformly dissolved in the organic solvent using a straight blade impeller at a speed of 280r / min. Then, organic additives were added, and the mixture was filtered and cooled to room temperature to obtain a viscous organic carrier.

[0039] (2) The conductive phase, glass phase and inorganic additives are premixed and dispersed to obtain inorganic mixed powder;

[0040] (3) The inorganic mixed powder is added to the organic carrier, premixed with a straight blade paddle mixer at a speed of 580 r / min, and then fully dispersed and uniformly dispersed through a three-roll mill until the scraper particle size is less than 5 μm, finally obtaining the resistance slurry.

[0041] Comparative Examples 1-4

[0042] The formulations of inorganic additives in the lead-free resistor pastes described in Comparative Examples 1-4 of this application are shown in Table 1, the formulations without organic components are shown in Table 2, the formulations of the glass phase are shown in Table 3, the formulations of the organic components are shown in Table 4, and the formulations of the lead-free resistor pastes are shown in Table 5. The preparation method of the lead-free resistor paste includes the following steps:

[0043] (1) At 80℃, the resin was uniformly dissolved in the organic solvent using a straight blade impeller at a speed of 280r / min. Then, organic additives were added, and the mixture was filtered and cooled to room temperature to obtain a viscous organic carrier.

[0044] (2) The conductive phase, glass phase and inorganic additives are premixed and dispersed to obtain inorganic mixed powder;

[0045] (3) The inorganic mixed powder is added to the organic carrier, premixed with a straight blade paddle mixer at a speed of 580 r / min, and then fully dispersed and uniformly dispersed through a three-roll mill until the scraper particle size is less than 5 μm, finally obtaining the resistance slurry.

[0046] Table 1

[0047]

[0048]

[0049]

[0050]

[0051] Table 2

[0052]

[0053]

[0054]

[0055]

[0056] Table 3

[0057] <![CDATA[SiO2]]> High <![CDATA[Al2O3]]> ZnO Bag SrO <![CDATA[B2O3]]> <![CDATA[Na2O]]> G1 42 5 10 10 6 7 10 10 G2 30 10 14 5 8 9 15 9 G3 34 2 2 20 10 1 20 11 G4 50 7 8 15 2 4 5 9 G5 56 1 20 1 4 1 8 9 G6 33 0 1 15 10 0 30 11 G7 40 0 25 1 0 10 15 9

[0058] Table 4

[0059]

[0060]

[0061]

[0062]

[0063] Table 5

[0064]

[0065]

[0066]

[0067] Performance metrics and testing methods

[0068] The mass ratio of the first additive and the second additive, as well as the mass ratio of ruthenium oxide to the first additive and the second additive, were all determined by X-ray photoelectron spectroscopy (XRF). The particle size ratio of the first additive and the second additive was obtained by photographing the particles of the first additive and the second additive using SEM and measuring their particle size.

[0069] (1) Application of resistive paste in the preparation of chip resistors: Sample preparation:

[0070] Using the resistive layer size (effective size 1mm*1.32mm, sintered film thickness 6~12μm) of 1206 chip resistors as test samples, the resistive paste of the examples and comparative examples was printed on an alumina substrate by screen printing. After sintering in an air atmosphere at 650℃~950℃ (the samples of the examples and comparative examples were all sintered at 820℃), 100 test samples were obtained. The test results are shown in Table 6 below.

[0071] (1-2) Shear resistance test:

[0072] The resistance value Ri of each of the above-prepared test samples was measured using a resistance measuring machine, and the average resistance value of all test samples was calculated.

[0073] (1-3) Temperature coefficient of resistance (TCR):

[0074] The samples were kept at constant temperatures of 25℃, -55℃, and 125℃ for 10 minutes respectively. The resistance of the samples was tested and the TCR was calculated according to the following formula.

[0075]

[0076] The cold TCR (CTCR) is calculated at a temperature of ~55℃, and the hot TCR (HTCR) is calculated at a temperature of 125℃; the resistor performance is qualified when the CTCR and HTCR are within ±100ppm / ℃.

[0077] (1-4) Antistatic properties (ESD):

[0078] Set the voltage to 3KV, apply the voltage to each component three times at ±3KV, let it stand for 15 minutes, and then test the resistance change rate. A resistance change rate within ±3.0% is considered acceptable.

[0079] Table 6

[0080]

[0081]

[0082] According to the data in Table 6, when the lead-free resistor pastes prepared in Examples 1 to 25 of this application are applied to chip resistors, the ESD performance is within the acceptable range and the TCR width is within ±50ppm / ℃.

[0083] Example 8: Due to the excessively large particle size ratio of the first additive and the second additive (i.e., the particle size of the first additive is too large relative to the second additive), the TCR of the product increases positively, and the HTCR exceeds 50 ppm / ℃. Example 9: Due to the excessively small particle size ratio of the first additive and the second additive (i.e., the particle size of the first additive is too small relative to the second additive), the ESD performance is low, reaching -2.99%. Example 14: Due to excessive amounts of the first and second additives, the conductive chains in the resistive element are loosely distributed, causing the conductor to break down, resulting in low ESD performance. Example 16: Due to insufficient amounts of the first and second additives, the conductive particles in the resistive element are not easily dispersed evenly, resulting in many soft agglomerated conductive particles. After high-voltage discharge, the impedance of the soft agglomerated state is conducted, leading to high ESD performance. Example 13: Due to insufficient amounts of the second additive; Example 15: Due to excessive amounts of the second additive, ESD performance also deteriorates to varying degrees.

[0084] Comparative Example 1, due to the absence of the second additive, and Comparative Example 2, due to the absence of the first additive, both had ESD performance outside the acceptable range, and the HTCR or CTCR widths both exceeded the range of ±100ppm / ℃. Comparative Example 3, due to the excessive addition of the first additive, resulted in ESD failure. Comparative Example 4, due to the excessive addition of the second additive, resulted in TCR failure and increased resistance.

[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application and are not intended to limit the scope of protection of this application. Although this application has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of this application without departing from the substance and scope of the technical solutions of this application.

Claims

1. A lead-free resistor paste, characterized in that, The lead-free resistor paste includes inorganic and organic components; The inorganic components include a conductive phase, a glassy phase, and inorganic additives; The organic components include resins, organic solvents, and organic additives; The conductive phase includes ruthenium oxide; The inorganic additive includes a first additive and a second additive; the first additive includes at least one of copper oxide and cuprous oxide, and the second additive includes niobium oxide; the mass ratio of the first additive to the second additive is first additive: second additive = 1:(2~5); The mass ratio of ruthenium oxide, the first additive, and the second additive is ruthenium oxide : first additive : second additive = 1 : (0.05~0.25) : (0.2~0.6); The particle size ratio of the first additive to the second additive is 1:(0.3~1); Based on the total mass percentage of the resistive paste being 100%, the mass percentage of the inorganic component is 50%~70%, and the mass percentage of the organic component is 30%~50%. Based on the total mass percentage of inorganic components being 100%, the mass percentage of the conductive phase is 5% to 40%, the mass percentage of the glass phase is 50% to 90%, and the mass percentage of the inorganic additives is 0.1% to 20%. Based on a total organic component mass percentage of 100%, the resin mass percentage is 1% to 20%, the organic solvent mass percentage is 60% to 90%, and the organic additive mass percentage is 0.5% to 20%.

2. The lead-free resistor paste as described in claim 1, characterized in that, The specific surface area of ​​the ruthenium oxide is 10~70m². 2 / g.

3. The lead-free resistor paste as described in claim 1, characterized in that, Includes at least one of (a) to (c) below: (a) The resin includes at least one of methylcellulose, ethylcellulose, acrylic resin, epoxy resin and alkyd resin; (b) The organic solvent includes at least one of terpineol, diethylene glycol monobutyl ether, tributyl citrate, diethylene glycol dibutyl ether, butyl carbitol and dibutyl phthalate; (c) The organic additives include at least one of polyethylene wax, polypropylene wax, polyamide wax, hydrogenated castor oil, organobentonite, polyamide, polyacrylate, phosphate ester, organosiloxane, polyether, polyethylene glycol and polydimethylsiloxane.

4. The lead-free resistor paste as described in claim 1, characterized in that, Based on a total mass percentage of 100% for the glass phase, the glass phase comprises the following components by mass percentage: SiO2 30%~56%, CaO 0~10%, Al2O3 1%~25%, ZnO 1%~20%, BaO 0~10%, SrO 0~10%, B2O3 5%~30%, and Na2O 9%~11%.

5. The lead-free resistor paste as described in claim 1, characterized in that, The inorganic additives also include at least one of silicon oxide, aluminum oxide, and zirconium silicate.

6. The lead-free resistor paste as described in claim 1, characterized in that, In the inorganic components, the average particle size of the conductive phase is 0.1~10μm; the average particle size of the glass phase is 0.5~2μm; and the average particle size of the inorganic additives is 0.1~5μm.

7. The method for preparing the lead-free resistor paste according to any one of claims 1 to 6, characterized in that, Includes the following steps: (1) The resin is heated and dissolved in an organic solvent, then an organic additive is added, and the organic carrier is obtained after filtration and cooling; (2) Mix and disperse the components in the inorganic component to obtain an inorganic mixed powder; (3) The inorganic mixed powder is added to the organic carrier and dispersed evenly to obtain the lead-free resistor paste.

Citation Information

Patent Citations

  • Lead-free thick film resistor composition and lead-free thick film resistor

    CN116994844A